KONSISTENSI PENGGUNAAN METODE PENERJEMAHAN LAFAZ RAḤMĀN DALAM “AL-QUR’AN DAN TERJEMAHANNYA EDISI PENYEMPURNAAN 2019” KARYA KEMENAG RI - Hilmi, Hafidzatul; Najib, Muhammad (AL ITQAN: Jurnal Studi Al-Qur'an, 2021)
This article presents an analytical study of the consistency of the use of the translation method used by the Ministry of Religion of the Republic of Indonesia in the "Al-Qur`an and its Translation for the 2019 Completion Edition". The focus of this research is on the methods, procedures, and translation techniques used in translating Raḥmān's word to confirm the inconsistencies found. Judging from Newmark's theory related to translation methods, procedures, and techniques, this analysis leads to the conclusion that Raḥmān's word is consistently translated only in 1 verse because of the demands of the context at hand, namely in surah al-Isrā' [17]:110, while the others indicated inconsistency. This inconsistency occurs based on three things, namely 1) the chosen diction/translation word, 2) the technique or procedure used, namely the provision of explanatory words, either in brackets or not, and 3) the possibility of typos. Judging from the diction used, there are two choices of words used to translate Raḥmān's word, namely "Maha Pemurah" and "Maha Pengasih". There are 4 methods found in translating the two words, namely faithful translation method, transfer or transliteration procedure, note-taking procedure, and description technique.